ANTI-INFLAMMATORY AND ANTIOXIDANT ACTIVITIES OF Phenax rugosus (POIR.) WEDD AND Tabebuia chrysanta G. NICHOLSON ACTIVIDAD ANTIINFLAMATORIA Y ANTIOXIDANTE DE Phenax rugosus (POIR.) WEDD Y Tabebuia chrysanta G. NICHOLSON - Luis F OSPINA G (Universidad de Antioquia, 2011)
Inflammation is a multifactorial and highly regulated process associated to several chronic and degenerative diseases. Due to the fact that many inflammatory processes are sometimes characterized by oxidative stress, it has been demonstrated that antioxidants are useful as anti-inflammatory agents. Phenax rugosus (Poir.) Wedd and Tabebuia chrysanta G. Nicholson species are used in the Colombian region called ''Eje Cafetero'' due to their antiinfeccious and immunomodulatory properties. In vivo anti-inflammatory and in vitro antioxidant properties of methanolic and aqueous extracts of the previously mentioned plant species were evaluated in this research. Two acute inflammation models were used for such purpose: TPA-induced mouse ear oedema and carrageenan-induced rat paw oedema. In vitro hydroxyl, peroxyl and superoxide scavenging activity of the extracts was evaluated. The aqueous extract of Phenax rugosus was found to be promising due to its anti-inflammatory and antioxidant activities. Results obtained from this research are a support for the ethnopharmacological use of these plant species. La inflamación es un proceso multifactorial y altamente regulado que acompaña a una gran variedad de patologías crónicas y degenerativas. Dado que muchos procesos inflamatorios crónicos se acompañan de estrés oxidativo, se ha demostrado que extractos y/o compuestos captadores de radicales libres son eficaces como antiinflamatorios. Las especies Phenax rugosus (Poir.) Wedd y Tabebuia chrysanta G. Nicholson son empleadas en la región cafetera colombiana y se les atribuyen propiedades antiinfecciosas e inmunomoduladoras. En el presente estudio se evaluaron las propiedades antiinflamatorias in vivo y antioxidantes in vitro de los extractos acuosos y metanólicos de estas dos especies vegetales. Se emplearon dos modelos de inflamación aguda: edema auricular inducido por TPA en ratón y edema plantar inducido por carragenina en ratas. La actividad antioxidante in vitro se evaluó frente a los radicales hidroxilo, peroxilo y superóxido. El extracto acuoso de Phenax rugosus resultó promisorio por sus actividades antiinflamatoria y antioxidante. Estos resultados contribuyen a dar un soporte científico al uso etnofarmacológico de las dos especies vegetales estudiadas.